Designing the 9th-Century-AD Vessel from Bozburun, Turkey - Harpster, Matthew (Wiley, 2009)
During the study of the 9th-century-AD vessel from Bozburun, Turkey, this author applied Richard Steffy's methodology which emphasizes the comprehensive deconstruction and step-by-step re-assembly of a vessel. This methodology, in turn, illuminated how the Bozburun ship was assembled and designed, and how this design process created particular components of the hull. This article discusses this design process, and how by understanding it we may also understand more about the people who made the Bozburun vessel.
Keywords: Richard Steffy; Bozburun; Turkey; ship design; mould frames; shipbuilders